A multisite study of nurse-reported perceptions and practice of ABCDEF bundle components. (October 2020) - Boehm, Leanne M.; Pun, Brenda T.; Stollings, Joanna L.; Girard, Timothy D.; Rock, Peter; Hough, Catherine L.; Hsieh, S. Jean; Khan, Babar A.; Owens, Robert L.; Schmidt, Gregory A.; Smith, Susan; Ely, E. Wesley
Abstract: Objectives: ABCDEF bundle implementation in the Intensive Care Unit (ICU) is associated with dose dependent improvements in patient outcomes. The objective was to compare nurse attitudes about the ABCDEF bundle to self-reported adherence to bundle components. Research methodology/design: Cross-sectional study. Setting: Nurses providing direct patient care in 28 ICUs within 18 hospitals across the United States. Main outcome measures: 53-item survey of attitudes and practice of the ABCDEF bundle components was administered between November 2011 and August 2015 (n = 1661). Results: We did not find clinically significant correlations between nurse attitudes and adherence to A wakening trials, B reathing trials, and sedation protocol adherence ( rs  = 0.05–0.28) or sedation plan discussion during rounds and A wakening and B reathing trial C oordination ( rs  = 0.19). D elirium is more likely to be discussed during rounds when ICU physicians and nurse managers facilitate delirium reduction ( rs  = 0.27–0.36). E arly mobilization is more likely to occur when ICU physicians, nurse managers, staffing, equipment, and the ICU environment facilitate early mobility ( rs  = 0.36–0.47). Physician leadership had the strongest correlation with reporting an ICU environment that facilitates ABCDEF bundle implementation ( rs  = 0.63–0.74). Conclusions: Nurse attitudes about bundle implementation did not predict bundle adherence. Nurse manager and physician leadership played a large role in creating a supportive ICU environment.